Reforming the lifeline program: Regulatory federalism in action?. (February 2019) - Jayakar, Krishna; Park, Eun-A
Abstract: This paper considers whether common national standards for determining participants' eligibility and designating service providers in the Lifeline program are preferable to a decentralized system where state utility commissions have greater influence over these program parameters. Two recent decisions of the Federal Communications Commission (FCC), a 2016 Order and its reversal in March 2017, on the designation of Eligible Telecommunications Carriers to provide broadband Lifeline service, centered on this question. Statistical analysis of program data demonstrates that state-by-state variations in enrollment may be attributed to state-level policy actions, after controlling for alternative demographic and economic explanations. This paper concludes that national standards may reduce state-by-state variations in program participation rates. Highlights: Investigates why Lifeline participation rates vary from state to state. Uses 2012 Lifeline reforms as natural experiment to study effects of de-enrollments. State-by-state variations in enrollment attributable to state-level policy actions. National standards may reduce state-by-state variations in participation rates.